Comparison of the efficiency and microbial mechanisms of chemical- and bio-surfactants in remediation of petroleum hydrocarbon. (1st December 2022) - Zhuang, Xuliang; Wang, Yaxin; Wang, Haoyu; Dong, Yuzhu; Li, Xianglong; Wang, Shijie; Fan, Haonan; Wu, Shanghua
Abstract: Surfactant-enhanced remediation (SER) is one of the most effective methods for petroleum hydrocarbon-contaminated sites compared to single physical and chemical methods. However, biosurfactants are not as commonly used as chemical surfactants, and the actual remediation effects and related mechanisms remain undefined. Therefore, to comprehensively compare the remediation effects and biological mechanisms of biosurfactants and chemical surfactants, soil column leaching experiments including two biosurfactants (rhamnolipids and lipopeptide) and three commercially used chemical surfactants (Tween 80, Triton X-100, and Berol 226SA) were conducted. After seven days of leaching, rhamnolipids exhibited the highest petroleum hydrocarbon removal rate of 61.01%, which was superior to that of chemical surfactants (11.73–18.75%) in n-alkanes C10–C30. Meanwhile, rhamnolipids exhibited a great degradation advantage of n-alkanes C13–C28, which was 1.22–30.55 times that of chemical surfactants. Compared to chemical surfactants, biosurfactants significantly upregulated the soil's biological functions, including soil conductivity (80.90–155.56%), and soil enzyme activities of lipase (90.31–497.10%), dehydrogenase (325.00–655.56%), core enzyme activities of petroleum hydrocarbon degradation, and quorum sensing between species. Biosurfactants significantly changed the composition of Pseudomonas, Citrobacter, Acidobacteriota, and Enterobacter at the genus level. Meanwhile, chemical surfactants had less influence on the bacterial community and interactions between species. Moreover, the biosurfactants enhanced the microbial interactions and centrality of petroleum hydrocarbon degraders in the community based on the network. Overall, this work provides a systematic comparison and understanding of the chemical- and bio-surfactants used in bioremediation. In the future, we intend to apply biosurfactants to practical petroleum hydrocarbon-contaminated fields to observe realistic remediation effects and compare their functional mechanisms. Graphical abstract: Image 1 Highlights: PHs removal by biosurfactants was 2.50–4.14 times higher than chemical surfactants. Biosurfactants regulated microbial communities and core enzyme activities in situ . Biosurfactants reinforced internal relations of microbial in co-occurrence network. Biosurfactants stimulated the potential microbial functions, such as quorum sensing. Systematic contrast of chemical and bio-surfactants brings insight into remediation.